Pameran RASA 2013 = RASA showcase 2013 / Wan Nur Khalisah Shamsudin...[et.al] - Shamsudin, Wan Nur Khalisah; Mohd Radzuan, Lili Eliana (Faculty of Art and Design, Universiti Teknologi MARA Melaka, Alor Gajah Campus, 2014)
Digital Art is a form of art that uses computer software to perform various technique such as manipulation, illustration, modification and many more. RASA is a digital art design showcase participated by 17 lecturers from Graphic Design & Digital Media Program. under the Faculty of Art & Design. UiTM Melaka. 17 artworks were displayed in art Gallery Pakus Halus. Bandar Hilir a modern and contemporary art gallery located in the heart of Melaka Historical City. The objective of the showcase is to increase awareness on digital art appreciation among the society especially when digital art do have a very high percentage of opportunity in promoting our treasure local elemen to the other country. Develop digital artist personality about art society among the academician in order to support the development of digital art such as art tourism in Malaysia.